Power conversion optimization for hydraulic systems controlled by variable speed drives. (February 2019) - Malrait, François; Jebai, Al Kassem; Ejjabraoui, Kamal
Highlights: Optimal energy function calculation for drive, motor and pumps is proposed. Induction motor losses including magnetic saturation are optimized. A geometrical approach is proposed to find the optimal pumps flow distribution. Abstract: Pumps are widely used in various domestic and industrial applications, such as in water and waste water, food and beverage, and oil and gas applications. In most cases, a pump is controlled by an asynchronous motor which converts the electrical power into the mechanical power required for the pump operation. The motor can be either connected directly to the mains (DOL) or controlled by a variable speed drive (VSD). The energy management of a global pumping system becomes very important to reduce the energy cost of the installations and optimize the maintenance cost, for instance, by increasing the lifetime of the equipment. A VSD is essential to increase the energy efficiency of the overall pump system. A VSD allows delivering all possible mechanical working points (speed, torque), and consequently, only the mechanical power required by the system. Furthermore, a VSD plays an important role in optimizing the electrical energy consumed by the motor as a function of the mechanical energy provided to the pump. This is achieved by minimizing the electrical heat energy losses. In this paper, we propose an original method for electrical energy optimization for a complete pump system including a motor and drive. The objective is to determine the optimal pump speed that minimizes the electrical energy consumption for a hydraulic operating system point. We model the system including a VSD, a motor, a pump, and the hydraulic application. Subsequently, we define the process optimization problem for a single pump and multiple pumps systems. For the single pump system, we demonstrate that the solution of the optimization problem is equivalent to minimization of the drive and motor losses. For the multiple pumps system, we show that we must also optimize the pump losses. For the hydraulic system using multiple pumps, the process demand is actually shared between these pumps. Thus, the speed of each pump is set such that the total energy consumption of the global pumping system is optimized. The simulation and experimental results exhibit the relevance of this power optimization approach for hydraulic pumping systems.